The aadE*-sat4-aphA-3 Gene Cluster of Mycoplasma bovirhinis HAZ141_2 Undergoes Genomic Rearrangements Influencing the Primary Promoter Sequence - Inna Lysnyansky; Ilya Borovok (MDPI AG, 2021)
The 54 kb GC-rich prophage region of Mycoplasma bovirhinis HAZ141_2 contains three structural 'compartments', one of which is a highly transmittable cluster of three genes, aadE-like (aadE*), sat4, and aphA-3. In this study, we characterized recombination events and their consequences occurred within the aadE*-sat4-aphA-3 containing region. Analysis of this region revealed direct repeats (DRs) of 155 and invert repeats (IRs) of 197 base pairs (bps) each, flanking and overlapping with the primary promoter P* located upstream of the aadE*. Two recombination events, including inversions via both 197 and 155-bp IRs (the latter become inverted after the initial 197-bp IRs associated inversion) and the excision of the aadE*-sat4-aphA-3 cluster, were confirmed. Inversion via 155-IRs results in changes within the P* promoter region. Using Escherichia coli JM109 carrying plasmids containing derivatives of the aadE*-sat4-aphA-3 cluster, we validated the expression of those genes from different promoters. Our results showed no difference in the minimal inhibitory concentrations (MICs) to kanamycin and neomycin and only 2-fold decrease in MIC (from 512 to 256 μg/mL) to nourseothricin between the wild type and a P* derivative promoter. However, the MICs to kanamycin and neomycin were at least 4-fold lower in the construct where aphA-3 expressed under its P2 promoter (128 µg/mL) in comparison to the construct where aphA-3 expressed under P1" promoter located within the sat4 gene (512-1024 µg/mL). PCR confirmed the excision of the aadE*-sat4-aphA-3 cluster via 197- and 155-bp DRs, but no selection of antibiotic-sensitive M. bovirhinis were obtained after 100 passages in kanamycin-free medium.